Video Inspirasi B.J Habibie sebagai Edukasi Membangun Semangat Belajar di SMAN 2 Palangka Raya - Aysah, Nurul; Surawan, Surawan; Sofiyati, Laila Musfirah (Lembaga Yasin AlSys, 2025)
B.J. Habibie is an inspirational figure who cannot be separated from his significant contribution to advancing education and technology in Indonesia. B.J. Habibie can be a role model as a means of education and motivation to foster students' enthusiasm for learning. This needs to be considered, because the spirit of learning is important for students to have in influencing the learning process. The methods applied are, namely video viewing, lecture methods, discussions and questions and answers. The approach used is Service Learning which includes three main elements including reality, reflection, and reciprocal relationships. The service will be held on September 24, 2024 at SMAN 2 Palangka Raya. The results of service activities in fostering students' enthusiasm for learning through a video program showing inspirational stories of B.J. Habibie's life journey in pursuing education and realizing his dreams.